Frequent issues and lessons learned from EuroFlow QA - Kalina, Tomas; Brdickova, Nadezda; Glier, Hana; Fernandez, Paula; Bitter, Marieke; Flores-Montero, Juan; van Dongen, Jacques J M; Orfao, Alberto (Journal of immunological methods, 2019)
EuroFlow Quality Assessment was designed to provide a feedback on the quality of the standardization effort in executing the EuroFlow protocols for sample preparation and instrument setup. It was first beta-tested by the members of the EuroFlow consortium internally (2010-2013) and opened to the external participants from 2015 onwards. The goal of participation in the EuroFlow QA is to evaluate whether the technical quality of the data generated by the laboratory is comparable to the data of the EuroFlow members and thus if a non-EuroFlow member participant can use the EuroFlow reference sample database for his own patient evaluation. Also it assesses whether data are sufficiently standardized for automated population gating and alarm notification. By spring 2018, a total 87 laboratories from 32 countries on five continents have registered for the EuroFlow QA program. We evaluated 163 results of 2015-2016 QA rounds, where we noted clear improvement in the score of first-time participants (median score of 91% correct) when they participated second time or later (median score of 94% correct, p = 0,017), which was comparable to EuroFlow member scores (median score of 97% correct). Among frequent mistakes, we found non-adherence to the EuroFlow protocols (improper reagent used), improper gating and some compensation issues. In summary, we show that EuroFlow QA has a positive impact on improvement of standardized data quality of non-member laboratories adhering to the EuroFlow standard operating procedures and reagent panels.
Keywords: laboratoře; Flow cytometry; lidé; Reference Standards; EuroFlow; referenční standardy; Flow Cytometry; průtoková cytometrie; Laboratories; Quality assessment scheme; Standardization; testování odbornosti laboratoří; Laboratory Proficiency Testing; Humans